2′‐Deoxymugineic acid promotes growth of rice (Oryza sativa L.) by orchestrating iron and nitrate uptake processes under high pH conditions. (16th December 2014) - Araki, Ryoichi; Kousaka, Kayoko; Namba, Kosuke; Murata, Yoshiko; Murata, Jun
Summary Poaceae plants release 2′‐deoxymugineic acid (DMA) and related phytosiderophores to chelate iron (Fe), which often exists as insoluble Fe(III) in the rhizosphere, especially under high pH conditions. Although the molecular mechanisms behind the biosynthesis and secretion of DMA have been studied extensively, little information is known about whether DMA has biological roles other than chelating Fe in vivo. Here, we demonstrate that hydroponic cultures of rice (Oryza sativa) seedlings show almost complete restoration in shoot height and soil‐plant analysis development (SPAD) values after treatment with 3–30 μm DMA at high pH (pH 8.0), compared with untreated control seedlings at normal pH (pH 5.8). These changes were accompanied by selective accumulation of Fe over other metals. While this enhanced growth was evident under high pH conditions, DMA application also enhanced seedling growth under normal pH conditions in which Fe was fairly accessible. Microarray and qRT‐PCR analyses revealed that exogenous DMA application attenuated the increased expression levels of various genes related to Fe transport and accumulation. Surprisingly, despite the preferential utilization of ammonium over nitrate as a nitrogen source by rice, DMA application also increased nitrate reductase activity and the expression of genes encoding high‐affinity nitrate transporters and nitrate reductases, all of which were otherwise considerably lower under high pH conditions. These data suggest that exogenous DMA not only plays an important role in facilitating the uptake of environmental Fe, but also orchestrates Fe and nitrate assimilation for optimal growth under high pH conditions.